High-Rate Solid-Liquid Separation Coupled With Nitrogen and Phosphorus Treatment of Swine Manure: Effect on Water Quality - Vanotti, Matias B.; Ro, Kyoung S.; Szogi, Ariel A.; Loughrin, John H.; Millner, Patricia D. (Frontiers in Sustainable Food Systems, 2018)
This study determined the water quality improvements in swine lagoons by an innovative swine manure treatment system operating at full-scale during five pig production cycles. The system performed high-rate solid-liquid separation, biological ammonia treatment and phosphorus treatment. The treatment system met the environmental performance standards for swine waste management systems in new or expanding operations in North Carolina. The system substantially reduced odor by 99.9%; pathogens by 99.99%, nutrients (phosphorus and nitrogen) by > 90%, and heavy metals by 99%. As the treated effluent and/or rainwater renovated the liquid in the anaerobic lagoons, they became aerobic (Eh > 300 millivolts). By the end of the second year, the NH4-N concentration in the lagoons liquid declined from the initial 370–485 mg L−1 to lower than 15. After conversion, the sludge accumulation in the former lagoons was halted. This was a significant outcome because one converted lagoon served twice the number of animals than before implementation of the innovative manure treatment system, which is similar to a situation of herd expansion. These findings showed that environmentally superior waste management technologies can have substantial positive impacts on water quality in intensive swine production.